Transformational Leadership Competency Requirements for University Counselors in the Digital-Intelligence Era: A Mixed-Methods Study at a Chinese Undergraduate Institution - Siqi , Chen; Fuyuan, Sun; Nualkham, Alinajitta (Rajapark Journal, 2025)
This study aims to explore 1) the current state of transformational leadership among university counselors in the context of digital intelligence, 2) the core competency requirements to enhance transformational leadership, and 3) the pathways to develop these competencies. The sample consisted of counselors from a Chinese undergraduate university, and the study used a mixed-methods design combining a questionnaire survey and semi-structured interviews. The quantitative phase employed a structured questionnaire assessing the four dimensions of transformational leadership, and the qualitative phase employed thematic analysis of interview data. To ensure methodological transparency and robustness, we conducted descriptive statistics alongside reliability and validity tests. The findings reveal that, in the digital-intelligence era, the overall level of transformational leadership among counselors is moderate, with uneven development across different dimensions. Specifically, intellectual stimulation and individualized consideration were relatively intense, while inspirational motivation and idealized influence require improvement. Additionally, counselors need significant improvement in competencies such as the use of digital intelligence tools, data analysis skills, online values education, and social media influence. The study proposes a three-dimensional optimization framework— “competency reconstruction, mechanism coordination, and technology empowerment” — to guide university counselors in improving their transformational leadership in the digital-intelligence context. This framework translates mixed-methods evidence into actionable pathways by aligning targeted training, full-cycle leadership management, and intelligent service platforms. Theoretically, the study refines the application of Bass and Avolio’s four-dimensional model to digital-intelligence contexts by clarifying competency structures and boundary conditions; practically, it offers concrete implications for policy design, counselor training systems, and the digital transformation of ideological and political education in higher education.